Eruptive mechanism of phreatomagmatic volcanoes from the Pinacate Volcanic Field: comparison between Crater Elegante and Cerro Colorado, Mexico. - Martin, Ulrike; Nemeth, Karoly (Massey University., 2004)
No abstract available